Pengaruh Era Digital pada Pembentukan Karakter Anak di Sekolah Dasar - Sunandari Sunandari; Afifah Nur Amalia Sari; St Mustainah; Muh. Viftar; Nur Ummi Kalsum (Journal on Education, 2023)
The research method used in this article is a qualitative research method, which means the author only uses journal theory as a reference in writing this article. The purpose of this study was to find out how the influence of the digital era on the formation of children's character in elementary schools. Based on the research results, the authors found that in this digital era it greatly influences the formation of children's character which has a negative impact, especially on elementary school children because it makes the child addicted to playing gadgets and accessing the internet so that he spends his time just playing gadgets. This causes the insufficiency in carrying out other activities such as learning and playing with peers and also has an impact on children's growth and development and visual impairment.